The (CH3OH)-C-13 optically pumped far-infrared laser: New lines and frequency measurements - Moraes, João Carlos Silos [UNESP]; Bertolini, A.; Carelli, G.; Ioli, N.; Moretti, A.; Strumia, F. (Institute of Electrical and Electronics Engineers (IEEE), 1996)
We report 18 new laser lines from (CH3OH)-C-13 generated in an optically pumped far-infrared laser; the laser lines are in the range of 54.2-420 mu m and are all characterized in wavelength, polarization relative to the pumping CO2 radiation, and pump offset relative to the CO2 center frequency, the frequencies of seven of these new lines along with 10 previously reported lines were measured by an accurate heterodyne technique, mixing them in a metal-insulator-metal (MIM) point contact diode, with another laser line of known frequency.